2013
DOI: 10.1002/jsfa.6407
|View full text |Cite
|
Sign up to set email alerts
|

Influence of two hop (Humulus lupulusL.) varieties onin vitrodry matter and crude protein degradability and digestibility in ruminants

Abstract: Decreased DM and CP degradability and increased amount of rumen 'bypass' protein could lower the amounts of protein required by high-producing ruminant animals. However, this supposition needs a validation with in vivo trials.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
14
0
1

Year Published

2015
2015
2020
2020

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 14 publications
(17 citation statements)
references
References 14 publications
2
14
0
1
Order By: Relevance
“…At equal amounts of added hop cones, the variety Dana had a greater effect on in vitro gas and SCFA production, demonstrating that alfa-acids notably contribute to the altered rumen fermentation. A lower gas and SCFA productions indicate a lower nutrient degradation in the rumen, which confirmed the results of our in vitro degradability trial (Lavrenčič et al, 2014). In addition, Lavrenčič et al (2014) demonstrated that in vitro digestibilities of DM and CP were not affected by increasing concentration of hop cones.…”
Section: Discussionsupporting
confidence: 87%
See 2 more Smart Citations
“…At equal amounts of added hop cones, the variety Dana had a greater effect on in vitro gas and SCFA production, demonstrating that alfa-acids notably contribute to the altered rumen fermentation. A lower gas and SCFA productions indicate a lower nutrient degradation in the rumen, which confirmed the results of our in vitro degradability trial (Lavrenčič et al, 2014). In addition, Lavrenčič et al (2014) demonstrated that in vitro digestibilities of DM and CP were not affected by increasing concentration of hop cones.…”
Section: Discussionsupporting
confidence: 87%
“…A lower gas and SCFA productions indicate a lower nutrient degradation in the rumen, which confirmed the results of our in vitro degradability trial (Lavrenčič et al, 2014). In addition, Lavrenčič et al (2014) demonstrated that in vitro digestibilities of DM and CP were not affected by increasing concentration of hop cones. Thus, we can conclude that the supplementation of cow diet with hop cones could be beneficial for the animal performance, as they increase the amount of digestible 'bypass' nutrients.…”
Section: Discussionsupporting
confidence: 87%
See 1 more Smart Citation
“…Recent research has shown that hops decreased proteolysis in vitro (Lavrenčič et al . ). Ammonia production was also inhibited via antimicrobial action on the HAB (Flythe ; Flythe et al .…”
Section: Resultsmentioning
confidence: 97%
“…Research results indicate that hops could: decrease methane production [4], ameliorate rumen acidosis [5], decrease proteolysis [6] and decrease deamination of amino acids to ammonia [7]. Taken together, these factors lessen the environmental impacts of cattle production, and improve feeding efficiency, animal performance and wellbeing.…”
Section: Introductionmentioning
confidence: 99%